"From savages to soldiers" Igorot bodies, militarized masculinity, and the logic of transformation in Dean C. Worcester's Philippine photographs - Fernandez, Juan (2023)
This article argues that the photographic and textual portrayals of Igorot headhunters in Dean Worcester's work functioned beyond mere displays of "savage" masculinity. Photographs of Igorot men were the basis of Worcester's civilizational argument, whose logic of transformation depended on the valorization of the male Igorot body, which then was reconfigured into military potential and therefore employable by the colonial state to carry out projects of supposed pacification and uplift. This article examines Worcester's interventions among the Igorot of the Cordillera Central, including the physical manipulation of a specific photograph that purported to show Igorot men caught in the moment of their transformation.
Keywords: Headhunters; Colonies -- Administration, 1965-1986; Igorot (Philippine people); Photographs